The 2025 Sumatra Flood in Al Jazeera Arabic Coverage: A Critical Discourse Analysis Based on Teun A. van Dijk’s - Aflaha Darajati; Gufron Gufron (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to examine Al Jazeera Arabic’s coverage of the 2025 floods in Sumatra, as presented on its YouTube channel, and to analyze the discourse representation through the lens of Teun A. van Dijk’s Critical Discourse Analysis. This study employs a descriptive qualitative approach, focusing on the live broadcasts reported by Sohaib Jazeem from the affected areas in Aceh. Data were collected through listening, note-taking, and translation, and subsequently analyzed using the Miles and Huberman model. The results indicate that the coverage emphasizes issues of environmental crisis, the impact of the disaster, and the conditions of the victims. At the macro level, the main theme relates to the environmental crisis, while at the superstructure level, comparisons are drawn with the 2004 tsunami to build audience understanding and provide an introductory overview of the natural destruction, which nearly matched the scale of the tsunami event. At the micro-structural level, the emphasis on victim data and aid distribution reveals a specific focus on three aspects: 1) the nature of the environmental damage, 2) the lack of accountability among authorities, and 3) the government’s inadequate response to flood victims. In addition to these three aspects of the text structure, this study is also informed by social cognition or social class position and social context—specifically, the prevailing knowledge or values within society—which also influence the analytical perspective. This study demonstrates that media coverage helps shape the public’s perspective on disaster events.